Pengaruh Financial Distress, CSR Disclosure, Dan Earnings Quality Terhadap Firm Value Yang Dimoderasi Liquidity - Aprilia Zahra Adisti; Nera Marinda Machdar (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to examine the influence of financial distress, corporate social responsibility disclosure and earnings quality on firm value with liquidity as a moderating variable. This type of research uses a qualitative descriptive method for literature study. The research results show that financial distress has a positive effect on firm value; corporate social responsibility disclosure has a positive effect on firm value; earnings quality has a positive effect on firm value; liquidity can strengthen the influence of financial distress on firm value; liquidity can strengthen the influence of corporate social responsibility disclosure on firm value and liquidity can strengthen the influence of earnings quality on firm value.